2019
DOI: 10.1016/j.jsps.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A study of the role of DIO1 and DIO2 polymorphism in thyroid cancer and drug response to therapy in the Saudi population

Abstract: BackgroundDeiodinases comprise a group of selenoproteins that regulate the bioavailability of active thyroid hormones (TH) in a time and tissue specific fashion. They increase the hormonal activity by metabolizing their inactive precursors to active forms or terminate their activity by deactivating active hormones. The role of the deiodinase (DIO) gene polymorphisms in thyroid cancer is not fully understood yet. This study evaluated the potential association of the DIO1 and DIO2 genes with differentiated thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[ 9 ] No association between DIO2 SNP and thyroid cancer manifestation was observed in this study which is in accordance with previous studies. [ 15 16 28 ] Thyroidectomized DTC patients lack inherent T3 production and hence entirely depend on the DIO1 and DIO2 enzymes for catalytic conversion of L-T4 to T3. DTC patients are given L-T4 therapy to suppress TSH activity to keep the remnant malignant thyroid tissues dormant to inhibit the recurrence of thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] No association between DIO2 SNP and thyroid cancer manifestation was observed in this study which is in accordance with previous studies. [ 15 16 28 ] Thyroidectomized DTC patients lack inherent T3 production and hence entirely depend on the DIO1 and DIO2 enzymes for catalytic conversion of L-T4 to T3. DTC patients are given L-T4 therapy to suppress TSH activity to keep the remnant malignant thyroid tissues dormant to inhibit the recurrence of thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…have speculated that DIO2 SNPs may have an important role in determining the L-T4 dose requirement in thyroidectomized and 131 I-treated DTC patients. [ 15 28 ] Torlontano et al . reported that the homozygous rs225014 variant was associated with approximately 20% higher L-T4 dose requirement to suppress TSH levels in DTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated the importance of DIO2 in patients with hypothyroidism; however, the effect of DIO2 polymorphism on BP in patients with hypothyroidism has not been identified. One study focused on the association between DIO1 and DIO2 variants in patients with thyroid cancer undergoing thyroidectomy and treatment with thyroxin [43]. They reported that participants with DIO2 polymorphism, rs1388378_G>T, required a higher hormonal dose; however, they did not suggest the influence of DIO2 polymorphism on disease status or other clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…When we evaluate the compromising 21 nodes of this PTC‐module, we find that several of these genes have already been individually associated with thyroid cancer, which further strengthens our confidence in our observations when we consider them as systems biomarkers. The following genes: PROS1, 42 DCSTAMP, 43 DUSP5, 44 AHNAK2, 45 SLC34A2, 46 FN1, 47 C16orf89, 48 FHL1, 49 TPO, 50 DIO1 51 has been associated with thyroid cancer and/or PTC.…”
Section: Discussionmentioning
confidence: 99%